Electoral impacts of uncovering public school quality: Evidence from Brazilian municipalities - Sergio Firpo; Renan Pieri; André Portela Souza (Institute for the Study of Labor (IZA), 2012)
School accountability systems that establish the adoption of incentives for teachers and school managers usually impact positively students' performance. However, in many circumstances, school accountability systems may face institutional restrictions to establish rewards and sanctions to administrators. In that aspect, the Brazilian accountability system is an interesting example: Most of primary public schools are run by municipal officials and federal government cannot enforce the adoption of incentives at local level. However, because mayors of Brazilian municipalities are the ultimate responsible for public elementary education we provide evidence that in 2008 local election, just some months after the publication of the second wave of a new evaluation of public schools run every two years by federal government, mayors became electorally accountable for not improving school quality. The results show that, on average, one point increase in a 0-10 scale index from 2005 to 2007 increased by around 5 percentage points the probability of re-election. This effect is even greater in localities with lower per capita income and those where the fraction of children at school age is larger. Therefore, electoral accountability may play a complementary role in school accountability systems that had not yet been fully exploited by education and political economics and political science literatures.
urn:nbn:de:101:1-2012081412499
Keywords: H11; H41; H52; H72; I21; I28; 330; public education; school accountability; electoral accountability; mayoral re-election races; Schule; Dienstleistungsqualität; Kontrolle; Wiederwahl; Kommunalwahl; Brasilien